2005
DOI: 10.1037/0021-843x.114.2.291
|View full text |Cite
|
Sign up to set email alerts
|

Four Studies on How Past and Current Suicidality Relate Even When "Everything But the Kitchen Sink" Is Covaried.

Abstract: T. E. Joiner's (2004, in press) theory of suicidal behavior suggests that past suicidal behavior plays an important role in future suicidality. However, the mechanism by which this risk is transferred and the causal implications have not been well studied. The current study provides evaluation of the nature and limits of this relationship across 4 populations, with varying degrees of suicidal behavior. Across settings, age groups, and impairment levels, the association between past suicidal behavior and curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
231
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 304 publications
(256 citation statements)
references
References 53 publications
21
231
1
3
Order By: Relevance
“…Conversely, one may have suicidal desire, but lack the capability to die by suicide. The relative rarity of the intersection of these factors is consistent with the relative rarity of death by suicide (Joiner, 2005;Van Orden, et al, 2008).…”
Section: Introductionsupporting
confidence: 61%
See 4 more Smart Citations
“…Conversely, one may have suicidal desire, but lack the capability to die by suicide. The relative rarity of the intersection of these factors is consistent with the relative rarity of death by suicide (Joiner, 2005;Van Orden, et al, 2008).…”
Section: Introductionsupporting
confidence: 61%
“…Conversely, one may have suicidal desire, but lack the capability to die by suicide. The relative rarity of the intersection of these factors is consistent with the relative rarity of death by suicide (Joiner, 2005;Van Orden, et al, 2008).Impulsivity has also been associated with death by suicide and is one of the most frequently implicated risk factors for engaging in maladaptive behaviors, such as serious self-injury (Anestis, Selby, & Joiner, 2007). However, recent research has shown that although people who attempt suicide tend to be more impulsive than those who do not, the actual act of suicide is generally not done impulsively.…”
mentioning
confidence: 69%
See 3 more Smart Citations